2012
DOI: 10.1158/1078-0432.ccr-12-1632
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic BRAF(V600E) Promotes Stromal Cell-Mediated Immunosuppression Via Induction of Interleukin-1 in Melanoma

Abstract: Purpose In this study, we assessed the specific role of BRAF(V600E) signaling in modulating the expression of immune regulatory genes in melanoma, in addition to analyzing downstream induction of immune suppression by primary human melanoma tumor-associated fibroblasts (TAFs). Experimental Design Primary human melanocytes and melanoma cell lines were transduced to express WT or V600E forms of BRAF, followed by gene expression analysis. The BRAF(V600E) inhibitor vemurafenib was used to confirm targets in BRAF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
243
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(259 citation statements)
references
References 49 publications
12
243
0
4
Order By: Relevance
“…Highdose IL-1β administration causes broad inflammation and is accompanied by tissue damage and tumor invasiveness (24). In vitro analysis of melanocytes and melanoma cell lines showed that BRAF V600E increases, while BRAF V600E inhibition reduces, the transcription of IL-1α and IL-1β (25,26). In human thyrocytes, IL-1β alters the expression and localization of junction proteins (27).…”
Section: Discussionmentioning
confidence: 99%
“…Highdose IL-1β administration causes broad inflammation and is accompanied by tissue damage and tumor invasiveness (24). In vitro analysis of melanocytes and melanoma cell lines showed that BRAF V600E increases, while BRAF V600E inhibition reduces, the transcription of IL-1α and IL-1β (25,26). In human thyrocytes, IL-1β alters the expression and localization of junction proteins (27).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in MDA and tumor antigen expression was associated with enhanced antigen-specific T-lymphocyte recognition in vitro (21,22) and in clinical trial patients (24), providing the first evidence for combining vemurafenib treatment with T-lymphocyte-directed immunotherapy. BRAFi also enhances the levels of MHC molecules on melanoma cells, reverses immune suppression of T lymphocytes by inhibiting IL-1a and IL-1b (25), and inhibits VEGF secretion from tumor cells (26), providing an additional explanation for why T-cell recognition is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effects of these agents are mediated by cellular effectors of the immune system. This has provided a rationale for combining MAPK pathway inhibitors with immunotherapy, as BRAFi can sensitize BRAF-mutant melanoma cells to immune recognition and relieve immune suppression (21)(22)(23)(24)(25)(26). Amid the speculation as to the role for combined MAPK pathway inhibition and immunotherapy, the degree to which kinase inhibition, specifically dabrafenib and/or trametinib, may directly affect immune function remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of RAS and PI3K/AK3 pathways cooperates to inhibit lymphocytes' function and survival. [63]. Tumor-associated fibroblasts (TAFs) respond to IL-1 by upregulating an immunomodulatory transcriptional program resulting in the production of COX-2, PD-1 ligands, and chemokines, as well as in the amplification of IL-1 signaling (Fig.…”
Section: Pd-1/pd-l1 In Malignant Diseasesmentioning
confidence: 99%